384 Patient initiated follow up: experiences from a tertiary gynaecological oncology centre. (13th November 2020) - Fairley, H; Anderson, Y; Ang, C; Roberts, K; Manderville, H
Abstract : Introduction: With limited clinical evidence supporting traditional current clinical models for patient follow up post cancer treatment, there is a need to collate evidence to develop more robust protocols. There is a growing body of evidence supporting patient initiated follow up (PIFU). PIFU can lead to a more flexible, positive consultation, whilst also having a positive impact on resource utilisation. At the Northern Gynaecological Cancer Centre in Gateshead we aim to introduce a PIFU protocol based on patient experience. The aim of this project is to redesign and improve current follow up protocols. Methods: 7 focus groups of patients and their carers from the North East of England were set up. The aim was to determine the views and opinions on the acceptability of PIFU using semi-structured interviews. Outcomes measured were satisfaction with the information provided and impact on quality of life. Results: 58 participants were recruited to focus groups. Most participants thought follow up appointments were used to detect recurrences and found them reassuring. Most would have preferred to be seen at hospital because of this reason and so would not like a telephone or skype follow up. Conclusion: Most participants expressed a preference for hospital follow up this could be influenced by a lack of experience of alternatives. Our aim is to now explore PIFU experiences using information from questionnaires given to patients following treatment for endometrial cancer. If this transpires to be a positive experience and improve recurrence detection we aim to expand PIFU to ovarian cancer.